2022
DOI: 10.1021/acsapm.2c01534
|View full text |Cite
|
Sign up to set email alerts
|

Design of Highly Thermally Conductive Hexagonal Boron Nitride-Reinforced PEEK Composites with Tailored Heat Conduction Through-Plane and Rheological Behaviors by a Scalable Extrusion

Abstract: The challenge of developing highly thermally conductive polymeric composites to meet the growing thermal management demands has recently attracted a lot of attention. To achieve a through-plane thermal conductivity higher than 2 W/mK, a high filler concentration within the poly(ether ether ketone) (PEEK) matrix is required, thus adding to the complexity of polymer processing. In this study, an optimized twin-screw extrusion melt-compounding technique was developed by tuning the melt flow of unfilled PEEK, feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…In hBN/PEEK composites, our previous investigation has shown that at 60 wt% loading, a 4880% improvement in thermal conductivity of composite comes at an expense of a 30% reduction in the mechanical strength compared to neat PEEK. This reduction in strength is attributed to the undesired aggregation of hBN filler inside the polymer 15 . A similar reduction in mechanical strength of the 60 wt% hBN loaded elastomer polymeric composite was reported by Yu et al, 16 which they ascribed to the presence of stress concentration at the hBN/matrix interfaces.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In hBN/PEEK composites, our previous investigation has shown that at 60 wt% loading, a 4880% improvement in thermal conductivity of composite comes at an expense of a 30% reduction in the mechanical strength compared to neat PEEK. This reduction in strength is attributed to the undesired aggregation of hBN filler inside the polymer 15 . A similar reduction in mechanical strength of the 60 wt% hBN loaded elastomer polymeric composite was reported by Yu et al, 16 which they ascribed to the presence of stress concentration at the hBN/matrix interfaces.…”
Section: Introductionsupporting
confidence: 75%
“…A bespoke screw configuration was established during compounding by optimization of the number of mixing, kneading, and reverse elements to accommodate the high filler amount (i.e., 60 wt%) in the PEEK polymer based on our previous publication. 15,30 Prior to extrusion, PEEK granules, hBN powder, and TiO 2 powder were dried at 150 C for 4-6 h in vacuum. A 26 mm screw diameter and L/D ratio of 40 was used in the extrusion line.…”
Section: Manufacturing Of Peek/hbn/tio 2 Hybrid Compounds By Twin-scr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, excessively high‐BNNS loading results in a loss of mechanical characteristics and increases the complexity and cost of processing composites. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, excessively high-BNNS loading results in a loss of mechanical characteristics and increases the complexity and cost of processing composites. [31] In order to take advantage of the anisotropic heat conduction of BNNSs, various strategies have been dedicated to obtaining the well-ordered arrangement of BNNSs, such as magnetic field, [32] ice template, [33] vacuum-assisted, [34] doctor blading, [35] electrospinning [36] and 3D Printing. [37] Recent research has drawn considerable attention to hetero-structured fillers due to the synergistic improvement effects of avoiding the introduction of interfacial thermal resistances between different fillers and establishing an effective thermal conduction network.…”
Section: Introductionmentioning
confidence: 99%